Employer branding and psychological contract in family and non-family firms - Pimentel, Duarte Nuno Gonçalves (2021)
ABSTRACT: Purpose – The purpose of this paper is to assess differences between employees of family and non-family firms regarding their perceptions of employer branding and psychological contract levels. Moreover, focusing on family firms, the authors assess the relation between the employees’ perceptions of employer branding and the psychological contract levels. Design/methodology/approach – The empirical evidence is provided by a sample of 165 Portuguese employees, 76 employees of family firms and 89 non-family firms’ employees, who responded to a questionnaire that included employer branding and psychological contract measures. All respondents study in small and medium-sized private companies. Findings – The results confirmed the research hypotheses, suggesting that employees of family companies show higher perceptions of employer branding and psychological contract levels than employees of nonfamily companies. Results also reveal that the perceptions of employer branding are positively related to the psychological contract levels of the family firm’s employees. Originality/value – This paper aims to contribute to the literature by addressing two contemporary organizational aspects yet under-addressed in the comparison between family and non-family firms while pursuing to offer insights on the relationship between the perceptions s of employer branding and levels of the psychological contract of employees working in family firms.